Diseño y construcción de prótesis funcional para agenesia de mano tipo 3 controlada por señales mioeléctricas. (2021)
The figures for persons with disabilities recorded by the national Government in relation to the prognosis of congenital malformations in Colombia indicated that by 2017, 2.6% of the total population suffered from congenital malformations. This percentage shows a considerable number of people, who suffer in their daily lives an affectation that modifies to some extent the quality of life. Agenesis, for example, is classified as the absence or limitation of organ growth during the development of the individual. A specific case is type III digital agenesis, which represents 10% of live births with malformations and, as its name indicates, is characterized by manifesting itself in the hands. This variant of the pathology involves the impossibility of basic actions carried out by the limb, causing problems in those who suffer from socioeconomic and / or psychological aspects. It is common for patients to look for assistive technologies, such as orthopedic devices designed to replace the missing part of the body, with a functional and at the same time aesthetic purpose, the contributions of industrial prostheses, in their sophistication, correspond to arduous studies and analyzes of the needs of each pathology. However, prostheses can be expensive, difficult to access, poorly available, or incompatible with the patient's physiognomy. Based on the above, the present work seeks to develop a functional prosthesis for type III hand agenesis, with a function based on the collection of myoelectric signals (EMG) generated by the electrical signals produced by muscle contraction; which can be interpreted, filtered, characterized and classified; this enables the prosthesis to perform activities that simulate fundamental movements from the collected signal, potentially improving the patient's quality of life. In addition, making use of modeling and prototyping programs such as Solid edge, Proteus 8.8, Eagle, it is possible with 3D printing to obtain a custom design, according to the physiological characteristics of the individual. As described above, the development of the custom-made prototype for a patient with type 3 agenesis controlled with myoelectric impulses is carried out